Measuring structural change: The case of China, Malaysia, and Ghana - Badibanga, Thaddée; Diao, Xinshen; Roe, Terry; Somwaru, Agapi (Project MUSE, 2013)
We extend the methods developed by Hausmann and Klinger (2006) to measure and compare the dynamics of a country’s structural transformation and apply the methods to China, Malaysia, and Ghana over the period 1962–2000. The results show that the rate of structural transformation is proportionately higher when a country produces more compact clusters of capital and consumer durable goods which in turn appear to lead more rapidly into new varieties of goods of higher unit values. We find that China’s transformation is the result of increasing proximity of her production/export basket to capital goods and consumer durables and the increasing values of new products in these two clusters. Malaysia’s product space in 1962 contained fewer of the world’s cluster of industrial goods than did China’s. The country nevertheless achieved a more rapid pace of transformation in the late 1980s which reduced her structural gap with China. The structure of the Ghanaian economy, however, is stagnant over time, and the country’s production profile is dominated by primary goods of low value.